Characterization of the Mandate of Public Managers in Ecuador. An Approach to their Management from the Performance and Learning Cycles - Jara Iñiguez, Irma; Cevallos, Gabriel (Revista del CLAD Reforma y Democracia, 2022)
This article aims to identify the characteristics of the mandate of public sector managers in Ecuador. For this purpose, an exploratory and descriptive study is carried out based on the manager´s life cycle approach, which shows an inverted U-shaped relationship between tenure and performance. A survey is used as a data collection instrument in which subordinates are consulted regarding the performance of managers. This was applied to 52 public servants, experts in the subject, who collaborate in 33 public administration institutions. The analysis addresses the management of the authorities by differentiating their time in office, which is categorized as: less than 1 year, between 1 and 3 years, between 3 and 5 years and more than 5 years. As a result, their mandate is characterized from aspects related to their commitment, knowledge of the task, diversity of information used, interest in the task and power. It is evident that for managers at political-administrative levels, similar characteristics to the stages described are observed, such as response to the mandate and experimentation in periods between one and five years.